A CASE STUDY ON TIME-COST RELATING WITH BIM-3D-LASER SCANNING INTEGRATION IN CONSTRUCTION PROJECT - ALI, NABAZ MAWLOOD ALI (Fırat Üniveristesi, 2023)
Yapı sektörü, modernleşme ve sanayileşme süreçlerinde önemli bir rol oynamıştır, yanı sıra diğer ekonomik sektörler için altyapının gelişimini etkilemede. 3D lazer tarama bunlardan biridir. veri toplamak için şantiyenin farklı zamanlarda tarandığı gerçek iş verilerinin toplanmasına yönelik yöntem arasında dikkate alınan zaman aralığında gerçekleştirilen iş miktarlarını ölçmek için kullanılabilir. iki ardışık tarama. Fotogrametri, geometrik verilerin toplandığı diğer bir veri toplama yöntemidir. sitedeki bir nesnenin özellikleri, fotoğraf görüntüsünden oluşturulur. Bu tez, 3B tarama ve fotogrametriyi entegre etmek amacıyla kullanılan bir yöntemi sunmaktadır. proje. Önerilen teknik, şu anda yapım aşamasında olan bir bina kullanılarak gösterilmiştir. Proje yönetiminin karşılaştığı en zorlu zorluklardan biri, sıklıkla zaman kaybına neden olan ve çözünürlüğü düşük olan iş ilerlemesini ölçmektir. Sonuç olarak, bu tezin amacı, sanayi devriminin mevcut teknolojik gelişmelerinden yararlanarak miktar yönetimi sürecinin verimliliğini artırmak için pratik fikirler sunmaktı. Bu tez, bir BIM modelinin ve 3B lazer taramanın faydalarından ve özelliklerinden yararlanarak, bir BIM modelinin ve 3B lazer taramanın benimsenmesinin, miktar yönetimi sürecinin doğruluğunu ve verimliliğini artırma potansiyeline sahip olduğunu iddia etmektedir. Vaka çalışması, doğruluk ve verimliliği değerlendirmek için birkaç ortak aktiviteyi gösterdi.

The building industry has played an important part in the modernization and industrialization processes, as well as in influencing the development of infrastructure for other economic sectors. 3D laser scanning is one method for collecting real work data, in which the construction site is scanned at different times to gather data that can then be used to measure the quantities of work performed within the time interval considered between two consecutive scans. Photogrammetry is another method for data collection, in which the geometrical properties of an object on site are generated from its photo image. This thesis presents used a method, which integrates 3D scanning and photogrammetry in an effort to This thesis will describe a system that combines 3D scanning with photogrammetry in order to improve the speed and accuracy of data collecting from construction sites to assist progress assessment and controlling the project. The proposed technique is shown using a building that is currently under construction. One of the most challenging difficulties encountered by project management is the measurement of job progress, which frequently wastes time and has a low resolution. As a result, the purpose of this thesis was to provide practical ideas for improving the efficiency of the quantity management process by leveraging current technology advances of the industrial revolution. This thesis contends that by exploiting the benefits and characteristics of a BIM model and 3D laser scanning, adopting a BIM model and 3D laser scanning has the potential to improve the accuracy and efficiency of the quantity management process. The case study illustrated several common activities for assessing accuracy and efficiency.
İnşaat projesinde bım-3d-lazer tarama entegrasyonu ile ilgili zaman-maliyet üzerine bir vaka çalışması
Keywords: Mimarlık